The Effect of Current Ratio, Return of Equity, and Debt Equity Ratio on Stock Prices with Dividend Payout Ratio as a Moderating Variable - Nurdyane, Novalida; Yohanes Indrayono; Hari Gursida (Asosiasi Ahli Administrasi Indonesia, 2026)
This study aims to analyze the effect of Current Ratio, Return On Equity Debt to Equity Ratio, and Dividend Payout Ratio on Stock Prices in food and staple food retail subsector companies listed on the Indonesia Stock Exchange in the period 2019-2023. By using Purposive Sampling, 12 companies were selected as samples based on certain criteria and data analysis using multiple linear regression. The results show that Current Ratio, Return On Equity, Debt to Equity Ratio and Dividend Payout Ratio are negatively related to stock prices. Current Ratio and Debt to Equity Ratio are negatively related to Dividend Payout Ratio, while Return On Equity is positively related to Dividend Payout Ratio. The moderating variables between the Current Ratio, Return on Equity, and Debt to Equity Ratio and the Dividend Payout Ratio are positively related to Stock Price. This study provides new empirical insights into capital structure and profitability, particularly in the food and staple food retail subsector. In this regard, retail company management needs to maintain a balance between profitability and leverage, and utilize dividend policy as a strategic instrument to strengthen the company's positive signal to investors.